SENSORY-BASED LEARNING TO ENHANCE CONCENTRATION IN AUTISTIC CHILDREN - Lusia Renita Yuniarti; Muchamad Arif (E-Jurnal SPIRIT PRO PATRIA, 2025)
Children with autism spectrum disorder (ASD) often struggle with concentration due to sensory processing challenges, affecting their learning and emotional regulation. This study aimed to examine the implementation of a sensory-based learning model to enhance concentration in children with ASD who also exhibit moderate intellectual disability. Conducted at SLB Harapan Bunda, Surabaya, Indonesia, the research applied a qualitative case study approach, collecting data through observation, interviews, and documentation between May and June 2025. Results show that structured sensory activities—including vestibular, proprioceptive, tactile, and motor exercises such as balance tasks, trampoline jumping, swing therapy, and coordination training—significantly improved attention span, emotional regulation, and classroom engagement. Concentration increased from 3–5 minutes to 15–20 minutes, and impulsive behaviors were reduced. These findings demonstrate that sensory-based learning effectively supports autistic children’s readiness to learn and classroom participation. Successful implementation depends on teacher expertise, appropriate facilities, and collaboration with parents.